The determinants of management accounting performance among diploma in accountancy students at UiTM Kedah, UiTM Perlis and UiTM Perak / Noraini Abdul Rahim…[et al.] - Abdul Rahim, Noraini; Wan Abdullah, Wan Faizah; Marzuki, Marzlin; Abu Bakar, Siti Salmah (Research Management Institude, 2005)
The main objective of this study is to investigate the determinants that contribute to the success in the performances of Management Accounting 1(MAC 210) and 2 (MAC 260) of Diploma in Accountancy students at the northern campuses of Universiti Teknologi MARA (Kedah, Perlis and Perak). All the data were obtained from the Academic Affairs Department at the respective campuses, t-test, Pearson Correlations and Stepwise Multiple Regression arc used to analyze the data Findings show that the performance of students with SPM Accounting and SPM Additional Mathematics are higher for all management accounting courses. Students with SPM Economics performed lower for both courses but the difference is insignificant for Management Accounting 2. The results also show that SPM Accounting, SPM Additional Mathematics, SPM Mathematics and SPM Economics except for SPM English have low positive correlations for MAC 210 and MAC 260. For joint efect, only SPM Economics shows positive influence on both MAC performance. Interestingly, MAC 210 has no effect on MAC 260.